Descriptive Portrait of Teenagers' Interest in Bible Reading - Dwi Ariefin; Untari Prihatiningsih (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
Teenagers, aged between 13 to 19 years, are more interested in religion and spiritual matters than before. Their positive perception will foster interest in reading the Bible and following spiritual guidance. Information about youth's perception of Bible reading is needed. A survey with 90 questionnaires was distributed to Christian youth in a number of provincial capitals in Indonesia. The data is processed, analyzed, and presented in a qualitative descriptive manner. It was found that the perception of Christian youth about reading the Bible: 1) do it because the Bible is the Word of God. 2) agree as a useful and quite interesting activity. 3) still respect the printed Bible, and don't insist on using a digital Bible. 4) have spiritual independence. 5) agree persistence determines. 6) doubting the influence of friends on perseverance in reading the Bible. 7) Bible reading community can be good influence. 8) respect a spiritual person or organization. 9) ready to be nurtured spiritually through reading the Bible. The pressures of advances in digital technology and the Covid-19 pandemic are not enough to weaken the positive perception of today's youth towards Bible reading. Useful findings for spiritual directors in Bible reading assistance and spiritual guidance.